Analysis of polysiloxane fluid PFMS-5 by HPLC - G. N. Turkeltaub; E. A. Smirnova; E. A. Chernyshev* (Тонкие химические технологии, 2015)
Polymethylphenylsiloxane liquid PFMS-5 is used as a high temperature heat transfer fluid and a working fluid in the high-vacuum pumps. It is one of the most high-temperature stationary phases in gas chromatography. However, some samples have an upper temperature limit of 280 to 350°С. The composition of this fluid was studied by HPLC. For identification a set of compounds isolated by preparative gas chromatography was obtained. A previously synthesized product consisting of linear polymethylphenylsiloxanes with the number of silicon atoms from 3 to 120 was used. By using a diode array detector the UV-spectra of all the components in the obtained chromatogram were recorded. On the basis of these data it can be concluded that the liquid PFMS-5 consists of polymer homologues with the number of silicon atoms from 3 to 13. In addition to linear methylphenyloligosiloxanes methylphenylsiloxanes of other structure are present in the liquid. Linear methylphenyloligosiloxanes were identified